Cover crops associated with quinoa (Chenopodium quinoa Willd) in the Peruvian Altiplano: Erosion reduction, improved soil health and agricultural yield - Salcedo-Mayta, Selima (2022)
The Peruvian Altiplano presents increasing fertility losses, being susceptible to natural erosion. For many years, conventional agricultural management has generated losses of the topsoil and deterioration of soil properties, impacting in crop yields and deepening the degradation of this vulnerable ecosystem. The aim of this research was to determine the benefits of cover crops against erosion, soil health and quinoa yield. The trial was carried out in Huancarani and Cahualla towns, Mañazo district, Puno; with a randomized complete block design (RCBD) with four treatments: without cover and with clover (Medicago hispida G.), vetch (Vicia villosa) and mulch covers. We evaluated the physical, chemical, and biological characteristics of soil, the biomass of the cover crops and the quinoa yield. The results showed that the treatments with clover, mulch and vetch covers reduced soil erosion by 59.61%, 51.87% and 49.50%, respectively. Likewise, the use of clover and vetch covers increased organic carbon (29.71% and 31.16%), nitrogen (36.94% and 48.65%), and available phosphorus with clover cover (26.11%). Finally, clover cover associated with quinoa increased the yield of quinoa grain by 17% and reduced soil erosion significantly. These results show that cover crops have great potential for restoring soil health and improving yield.